THE RESEARCH ON THE PATH OF PROMOTING INDUSTRIAL INTEGRATION THROUGH E-COMMERCE DEVELOPMENT IN HANGZHOU UNDER THE CONTEXT OF THE DIGITAL ECONOMY - Gao , Xueyan; Chit, Alfred Chee Ah (INTERNATIONAL JOURNAL OF INNOVATION AND INDUSTRIAL REVOLUTION (IJIREV), 2026)
The rapid advancement of digital technology has profoundly reshaped consumer behavior, and the growth of the digital economy is accelerating industrial digitization and cluster formation. As a leading e-commerce hub in China, Hangzhou is well-positioned to integrate the digital and real economies by capitalizing on its strengths in digital commerce. However, challenges such as spatial constraints in industrial integration, bottlenecks in key resource flows, and barriers to cross-regional cooperation persist. Drawing on insights from cases such as Guangzhou-Foshan metropolitan integration, Tianlifang·Linping Future Farm, and New York’s Silicon Alley, this study proposes leveraging e-commerce as a catalyst for transformation. It highlights the role of e-commerce actors in refining demand alignment, resource distribution, and governance. Additionally, it emphasizes upgrading industrial, value, and benefit chains to build a resilient industrial ecosystem. The paper further recommends promoting urban-rural integration through core industry leadership, fostering resource sharing and cross-regional collaboration to enhance synergies between domestic and international trade, and coordinating living and production spaces through guided planning and talent mobility—all to support balanced and sustainable economic development.